2023
DOI: 10.3390/genes14030731
|View full text |Cite
|
Sign up to set email alerts
|

Using Next-Generation Sequencing to Disentangle the Diet and Incidence of Intestinal Parasites of Falkland Flightless Steamer Duck Tachyeres brachypterus and Patagonian Crested Duck Lophonetta specularioides Sharing a South Atlantic Island

Abstract: Species overlapping in habitat use can cohabit depending on how they exploit resources. To understand segregation in resource use, an exhaustive knowledge of the diet is required. We aimed to disentangle the diet composition of the Falkland Flightless Steamer Duck Tachyeres brachypterus and the Patagonian Crested Duck Lophonetta specularioides sharing a coastal environment. Using DNA extracted from scats and Illumina sequencing, we generated a list of molecular operational taxonomic units. Both ducks consumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Two articles in this Special Issue illustrate how DNA metabarcoding can resolve the dietary composition and trophic flexibility of polar organisms at an unprecedented taxonomic resolution. Masello et al [15] found that two duck species sharing a coastal environment in the Falklands/Malvinas exploited different prey species, with only the flightless steamer duck consuming fish. Males and females of this species were also found to eat different fish species, suggesting that dietary niche segregation occurs at both the inter-and intraspecific level.…”
Section: Dietary Studies To Identify Niche Separation and Predict Cli...mentioning
confidence: 99%
“…Two articles in this Special Issue illustrate how DNA metabarcoding can resolve the dietary composition and trophic flexibility of polar organisms at an unprecedented taxonomic resolution. Masello et al [15] found that two duck species sharing a coastal environment in the Falklands/Malvinas exploited different prey species, with only the flightless steamer duck consuming fish. Males and females of this species were also found to eat different fish species, suggesting that dietary niche segregation occurs at both the inter-and intraspecific level.…”
Section: Dietary Studies To Identify Niche Separation and Predict Cli...mentioning
confidence: 99%